Long term variability of Cygnus X-1 VII. Orbital variability of the focussed wind in Cyg X-1/HDE 226868 system - Grinberg, V.; Leutenegger, M. A.; Hell, Natalie; Pottschmidt, K.; Böck, Moritz; Garcia, J. A.; Hanke, Manfred; Nowak, M. A.; Sundqvist, J. O.; Townsend, R. H. D.; Wilms, Jörn (Astronomy & Astrophysics, 2015)
Binary systems with an accreting compact object off er a unique opportunity to investigate the strong, clumpy, line-driven winds of early-type supergiants by using the compact object's X-rays to probe the wind structure. We analyze the two-component wind of HDE 226868, the O9.7Iab giant companion of the black hole Cyg X-1, using 4.77 Ms Rossi X-ray Timing Explorer (RXTE) observations of the system taken over the course of 16 years. Absorption changes strongly over the 5.6 d binary orbit, but also shows a large scatter at a given orbital phase, especially at superior conjunction. The orbital variability is most prominent when the black hole is in the hard X-ray state. Our data are poorer for the intermediate and soft state, but show signs for orbital variability of the absorption column in the intermediate state. We quantitatively compare the data in the hard state to a toy model of a focussed Castor-Abbott-Klein wind: as it does not incorporate clumping, the model does not describe the observations well. A qualitative comparison to a simplified simulation of clumpy winds with spherical clumps shows good agreement in the distribution of the equivalent hydrogen column density for models with a porosity length on the order of the stellar radius at inferior conjunction; we conjecture that the deviations between data and model at superior conjunction could either be due to lack of a focussed wind component in the model or to a more complicated clump structure.
Keywords: stars: individual: Cyg X-1; X-rays: binaries; binaries : close; stars: winds; outflows